Cortical control of posture in fine motor skills: evidence from inter-utterance rest position - Easthope, Eric; Shamei, Arian; Liu, Yadong; Gick, Bryan; Fels, Sidney (Frontiers in Human Neuroscience, 2023)
The vocal tract continuously employs tonic muscle activity in the maintenance of postural configurations. Gamma-band activity in the sensorimotor cortex underlies transient movements during speech production, yet little is known about the neural control of postural states in the vocal tract. Simultaneously, there is evidence that sensorimotor beta-band activations contribute to a system of inhibition and state maintenance that is integral to postural control in the body. Here we use electrocorticography to assess the contribution of sensorimotor beta-band activity during speech articulation and postural maintenance, and demonstrate that beta corresponds to the inhibition of discrete speech movements and the maintenance of tonic postural states in the vocal tract. These findings identify consistencies between the neural control of posture in speech and what is previously reported in gross motor contexts, providing support for a unified theory of postural control across gross and fine motor skills.